2012
DOI: 10.1111/j.1600-0838.2010.01144.x
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors and prognostic indicators for medial tibial stress syndrome

Abstract: The objective of the study was to examine the risk factors and prognostic indicators for medial tibial stress syndrome (MTSS). In total, 35 subjects were included in the study. For the risk factor analysis, the following parameters were investigated: hip internal and external ranges of motion, knee flexion and extension, dorsal and plantar ankle flexion, hallux flexion and extension, subtalar eversion and inversion, maximal calf girth, lean calf girth, standing foot angle and navicular drop test. After multiva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
113
2
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(119 citation statements)
references
References 24 publications
(44 reference statements)
1
113
2
3
Order By: Relevance
“…The 21 included studies consisted of three cross-sectional,10 21 30 nine case–control7 8 11–15 20 31 and nine prospective cohort studies 2–4 9 16–19 22. In seven of the 21 studies, the participants were recreational athletes/physically active 7 10 11 14 15 20 30.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The 21 included studies consisted of three cross-sectional,10 21 30 nine case–control7 8 11–15 20 31 and nine prospective cohort studies 2–4 9 16–19 22. In seven of the 21 studies, the participants were recreational athletes/physically active 7 10 11 14 15 20 30.…”
Section: Resultsmentioning
confidence: 99%
“…Risk factors for MTSS have been studied in numerous individual studies. Researchers have examined many variables as potential risk factors for MTSS such as body mass index (BMI),4 7–9 bone geometry,10 gait kinematics,[11–14 leg length differences,12 navicular drop,9 15–20 range of motion (ROM),4 8 9 11 12 14 16 18 21 training history4 18 19 22 and others. Although the results of these individual studies can inform clinical practice, the reported findings are often based on small sample sizes with conflicting results.…”
Section: Introductionmentioning
confidence: 99%
“…7 The lower extremity injuries military recruits sustain have negative effects on morbidity, training time, financial resources, and staffing. 2,8,9 Based on research findings and practitioners' beliefs, experiences, biases, and paradigms, multiple risk factors are theorized for MTSS. 2 In the 21 studies the authors reviewed, more than 100 risk factors were proposed, yet only 9 risk factors were supported by moderate to strong evidence in clinical practice 5 : body mass index (BMI), navicular drop, ankle plantar-flexion range of motion (ROM), ankle-dorsiflexion ROM, ankle-eversion ROM, ankle-inversion ROM, quadriceps angle, hip internalrotation ROM, and hip external-rotation ROM.…”
Section: Commentarymentioning
confidence: 99%
“…This ailment has been associated with the presence of several risk factors such as training errors, decreased hip internal range of motion, increased ankle plantar flexion, positive navicular drop, female gender, increased body mass and foot hyperpronation [6][7][8][9][10][11][12][13].…”
mentioning
confidence: 99%